Open Culture Ethanol-Based Chain Elongation to Form Medium Chain Branched Carboxylates and Alcohols - de Leeuw, Kasper D.; Ahrens, Theresa; Buisman, Cees J. N.; Strik, David P. B. T. B. (Frontiers in Bioengineering and Biotechnology, 2021)
Chain elongation fermentation allows for the synthesis of biobased chemicals from complex organic residue streams. To expand the product spectrum of chain elongation technology and its application range we investigated (i) how to increase selectivity towards branched chain elongation and (ii) whether alternative branched carboxylates such as branched valerates can be used as electron acceptors. Elongation of isobutyrate elongation towards 4-methyl-pentanoate was achieved with a selectivity of 27% (of total products, based on carbon atoms) in a continuous system that operated under CO2 and acetate limited conditions. Increasing the CO2 load led to more in situ acetate formation that increased overall chain elongation rate but decreased the selectivity of branched chain elongation. A part of the in-situ acetate formation was related to alcohol formation that seemed to occur via hydrogenogenic ethanol oxidation thermodynamically coupled to hydrogentrophic carboxylate reduction. Several alcohols including isobutanol and n-hexanol were formed. The microbiome from the continuous reactor was also able to form small amounts of 5-methyl-hexanoate likely from 3-methyl-butanoate and ethanol as substrate in batch experiments. The highest achieved concentration of isoheptanoate was 6.4 ± 0.9 mM Carbon, or 118 ± 17 mg/L, which contributed for 7% to the total amount of products (based on carbon atoms). The formation of isoheptanoate was dependent on the isoform of branched valerate. While 3-methyl-butanoate was likely elongated to 5-methylhexanoate, a racemic mixture of L/D 2-methyl-butanoate was not. When isobutyrate and isovalerate were added simultaneously as substrates there was a large preference for elongation of isobutyrate over isovalerate. Overall, this work showed that chain elongation microbiomes can be further adapted with supplement of branched-electron acceptors towards the formation of iso-caproate and iso-heptanoate as well as that longer alcohol formation can be stimulated.